Digital Competencies, critical thinking and innovation: Systematic Mapping - Andrea Paola Velasco Donoso; Luis Arturo Rosero Constante; Vanny Karlina Centanaro Vega (Universidad Ciencia y Tecnología, 2022)
Technology is an extension of our body and is present in our daily lives, which has led to a narrow mindset that equates digital transformation with access to technology and the use of digital resources, believing that passive consumption of online content will contribute to a digital mindset. Digital transformationis not just about access to technology, but also about understanding and using technology to solve problems, and critical thinking is key to driving innovation. This study systematically maps the outcomes of educational practices that contribute to the development of digital competencies. Twenty-six articles related to the research topic were identified, which show that there is an absence of studying innovation as an effect of the appropriation of digital skills.